2001
DOI: 10.1128/jcm.39.12.4332-4338.2001
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Dengue Virus-Specific Serum Immunoglobulin Classes and Subclasses Correlate with Clinical Outcome of Infection

Abstract: The kinetics of dengue virus (DEN)-specific serum immunoglobulin classes (immunoglobulin M [IgM] andIgA) and subclasses (IgG1 to IgG4) were studied in patients suffering from dengue fever (DF), dengue hemorrhagic fever (DHF), and dengue shock syndrome (DSS). Serum samples from non-DEN febrile patients were included as controls. IgM, IgG1, and IgG3 serum antibodies were the predominant immunoglobulins throughout the course of illness in all three patient groups. In contrast, IgA antibodies were significantly hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
85
1
4

Year Published

2003
2003
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(94 citation statements)
references
References 22 publications
4
85
1
4
Order By: Relevance
“…and IgG at day 7 p.i (49). The kinetics of isotype production in the A/J mouse model parallels that in human cases, and human Abs against DEN presumably provide protection from reinfection (20,28). In a mouse model for DEN vaccine testing, immunization with DEN vaccine strains resulted in the production of neutralizing Ab titers and protection from lethal DEN challenge (21).…”
mentioning
confidence: 99%
“…and IgG at day 7 p.i (49). The kinetics of isotype production in the A/J mouse model parallels that in human cases, and human Abs against DEN presumably provide protection from reinfection (20,28). In a mouse model for DEN vaccine testing, immunization with DEN vaccine strains resulted in the production of neutralizing Ab titers and protection from lethal DEN challenge (21).…”
mentioning
confidence: 99%
“…However, both of these assays are laborious to perform and a period of at least 7 days is required to obtain accurate diagnostic results using them. Recently, several enzyme-linked immunosorbent assays (ELISAs) have become commercially available for the detection of DEN-specific antibodies of different isotypes (6,7).…”
mentioning
confidence: 99%
“…20 It has been reported that in individuals with FcγRIIa-R/R131 genotypes as the predominant polymorphic variants, IgG1 and IgG3 bind efficiently. 8,21 In addition, the signal generated after interaction between FcγRIIa and the virus-antibody (DENV/IgG1/3) complex may be associated with an efficient phagolysosome formation 22 and the elimination of the immune complex and control of viral dissemination.…”
Section: Discussionmentioning
confidence: 99%